Deterministic contribution of low symmetry phases to piezoresponse in oxide ferroelectrics. (15th February 2021) - Zou, M.J.; Tang, Y.L.; Zhu, Y.L.; Wang, Y.J.; Yang, L.X.; Ma, X.L.
Abstract: Giant piezoelectricity has been thought to be originated from polarization rotation, electric-field-induced phase transformation or nano-domain reorientation in diverse complicated morphotropic phase boundaries (MPB) based piezoelectric ceramics. However, the deterministic contribution to the peak piezoelectricity is still elusive. Here, a full stage of piezoelectric response is presented in pure PbTiO3 films epitaxially constrained as the monoclinic phase on SrTiO3 (111), where the as-prepared films feature complicated monoclinic nano-domains with 201 domain boundaries. By applying external voltage, the piezoelectric response undergoes three distinct stages which correspond, respectively, to the three existing mechanisms in terms of polarization rotation, nano-domain reorientation, and electric-field-induced phase transformation. A direct correlation between the electric-poling process and the piezoelectric response is established, confirming that the phase transformation from the monoclinic to tetragonal plays a dominant role for the superior piezoelectric properties of the oxide. This study clarifies the role of monoclinic phase by integrating the three individual mechanisms of piezoresponse into a single-phase perovskite oxide, which may facilitate the development of high-performance piezoelectric materials for electronic device applications. Graphical abstract: Image, graphical abstract